ASSESSMENT OF THE PATIENT’S ORGANS AND SYSTEMS BASED ON CHANGES IN THE CONTENT OF AUTOANTIBODY MARKERS - Kh. Kh. Gantseva; D. M. Gabitova; L. T. Suleymanova (Креативная хирургия и онкология)
In a normal immune  response develops only to foreign antigens or modified their own. Aging and certain diseases lead to the fact that there are antibodies directed against its own tissues,  which are perceived  as foreign tissue,  as antigens, develop  an autoimmune reaction.  The paper  presents data  on the  twenty-four natural autoantibodies to one  or more antigens of a particular organ  orientation.